Corpocracy : - Monks, Robert A. G. (John Wiley & Sons, 2008)
Shareholder control over large corporations is worryingly weak and the unrestrained hunt for profits is taking a toll on the environment and society. In Corpocracy, corporate lawyer, venture capitalist, and shareholder activist Robert Monks reveals how corporations abuse their power and what we the people must do to rein them in. In a clear and careful analysis, Monks outlines a plan for reconciling the competing interests of corporations and society through thoughtful shareholder activism.